Durability, Market Structure and New-Used Goods Models - Liebowitz, Stan J. (American Economic Review, 1982)
Focuses on the relationship between market structure and monopoly power. Durability models; New-used goods model; Durability and monopoly in the new-used model; Interdependence between market structure and durability. (Из Ebsco)